Perumusan Strategi Penguasaan Industri Maritim Untuk Memperkuat Pertahanan Negara - Nurcahya Dwi Asmoro; Budi Setiarso; Sukarno (Jurnal Optimasi Sistem Industri, 2018)
Natural resources and the strategic position of Indonesia in a cross position shipping lanes of the world contributed to having a great economic potential but also gives a serious impact threat. For that, it is needed a strong national defense in order to protect the sovereignty and territorial integrity of Indonesia. The overall defense system, involving the entire nation must be nurtured as directed. The national industry as one of the supporting components in the country's defense system should be controlled by domestic industry management, including the national industry in the sector of maritime transport means. Government's attention that supports the growth of maritime transport means is a great opportunity to boost the national economy as well as the preparations for war situations. Amid the possibilities and constraints, this study investigated the strategy for the control of the maritime industry to strengthen the country's defense. Mixed method research descriptive qualitative and quantitative SWOT analysis was used to investigate it. The study found that the strategy for the control of the maritime industry is to carry out the construction of port facilities, the construction of a fleet of ships made in the country, the formation of qualified human resources, to improve its management, ensure the availability of the main spare parts and improve shipbuilding capability, to optimize the benefits of sabotage principle to resolve banking policy which is still not very profitable to the industries.